Efficient solution-processed red all-fluorescent organic light-emitting diodes employing thermally activated delayed fluorescence materials as assistant hosts: molecular design strategy and exciton dynamic analysis. Issue 21 (22nd May 2017) - Chen, Dongjun; Cai, Xinyi; Li, Xiang-Long; He, Zuozheng; Cai, Chengsong; Chen, Dongcheng; Su, Shi-Jian
Abstract : Efficient Förster energy transfer process from TADF assistant hosts to fluorescent dye affords efficient solution-processed red OLEDs with a maximum EQE of 8.0%. Abstract : The strategy of employing highly soluble, thermally activated, delayed fluorescence (TADF) materials that possess small singlet–triplet splitting energies (Δ E ST ) for efficient reverse intersystem crossing (RISC) processes results in simplified and low-cost solution-processed all-fluorescence organic light-emitting diodes (OLEDs). However, confined by the energy gap law, it is difficult to strike a balance between a large singlet radiative rate constant ( k Sr) and very small electron exchange energy ( J ), which hinders the realization of highly efficient red TADF emission with short excited state lifetimes. Herein, via integrating assistant hosts with TADF character and conventional fluorescent dopants with a large k Sr, efficient solution-processed red all-fluorescent OLEDs with external quantum efficiency exceeding the theoretical maximum for traditional fluorescent devices (5%) were prepared. Exciton dynamic studies of the ternary system revealed that the rapid Förster energy transfer channel enabled the significant reduction of singlet and triplet exciton density, which contributed to the suppressed efficiency roll-off of OLEDs operating at high current density. Regarding TADF assistant host molecular design, maintaining a moderate k Sr for a large Förster energy transfer radius is as important as keeping a relatively small Δ E ST for efficient triplet exciton utilization in this ternary prototype.